A redação como ferramenta de avaliação e de seleção dos sujeitos no mercado de trabalho: outro olhar ao profissional da linguagem - Araújo, Luciana Kuchenbecker (2016)
The objective of this research is to investigate how two big companies from Goiânia-GO use the Composition Evaluation as a tool to evaluate the candidates during the selective admission processes; according to the observation and the evaluation practices of the Professional in the Human Resources area (HR),it aims to understand the conceptions of individual, language and text, also to find answers to the following questionings: i) the studies about language philosophy, especially in the Statement Linguistics Field (SL) – what is configured as the Candidates evaluation axis to enter the Federal Higher Education Institutions – are they able to dialogue, influence and contribute with other Human Sciences fields which also aim to anlyze the profile and some competencies of the individuals from their relationship to language.? ii) As they conceive the relationship between the individuals and the language as a cryterios to selection and admission of new coworkers, which conceptual bases about competency evaluation through written language are the HR Professional sharing? iii) besides the Recruitment and Selection (RS), is there an actuation for language Professional in the HR departments and in other fields of the companies? The SL suppositions, according to to Bakhtin’s studies (2003; 2006), and the contributions of Human Relationship Theory, based on Chiavenato’s works (2004; 2009), configure as theoretical methodological axis for the investigation of the relationships which are stablished respectively between the individual, the language and the text school and work spheres. The research was developed from the qualitative pradigm and divided in three phases, which are organized in ten stages. The first phase, the descriptive and ethnographic methodology was applied; in the second phase, a cooperative Action-Research was performed. and, in the third phase, the interpretation of the data generated from the two previous phases. The results of the investigations that were taken suggest that, though the companies convertge to SL conception, as they considere relevant to evaluate the relationship between individuas and language and raise the text as object of analysis and starting point to know the social man and his language, the conceptual bases shared by HR professionals and materialized in evaluative activities are several and not always harmonious among themselves. The results still point out that language professionals’ contributions, graduated from Faculty of Arts, besides the teaching practices and research, are greatly relevant to the HR department and to several areas of the organizational universe which demands habilities and competencies on the management of languages